2021
DOI: 10.1038/s41598-021-97101-0
|View full text |Cite|
|
Sign up to set email alerts
|

Aerobic exercise improves LPS-induced sepsis via regulating the Warburg effect in mice

Abstract: We investigated the impact of aerobic exercise (AE) on multiple organ dysfunction syndrome (MODS), aortic injury, pathoglycemia, and death during sepsis. ICR mice were randomized into four groups: Control (Con), Lipopolysaccharide (LPS), Exercise (Ex), and Exercise + LPS (Ex + LPS) groups. Mice were trained with low-intensity for 4 weeks. LPS and Ex + LPS mice received 5 mg/kg LPS intraperitoneally for induction of sepsis. Histopathological micrographs showed the organ morphology and damage. This study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Mitochondrial pyruvate dehydrogenase complex (PDC) catalyzes the irreversible decarboxylation of pyruvate, a product of glycolysis, to produce acetyl coenzyme A and enter the tricarboxylic acid cycle, thus playing a crucial role in cellular catabolic glucose pathway ( Stacpoole, 2017 ). The Warburg effect confirms that the marker of tumor metabolism is aerobic glycolysis rather than the mitochondrial oxidation of pyruvate ( Bencze et al, 2021 ; Wang, Wang & Tang, 2021 ; Wen et al, 2021 ). Studies have suggested that mitochondrial function is weakened by the inhibition of PDC, causing metabolic changes in tumor cells.…”
Section: Introductionmentioning
confidence: 72%
“…Mitochondrial pyruvate dehydrogenase complex (PDC) catalyzes the irreversible decarboxylation of pyruvate, a product of glycolysis, to produce acetyl coenzyme A and enter the tricarboxylic acid cycle, thus playing a crucial role in cellular catabolic glucose pathway ( Stacpoole, 2017 ). The Warburg effect confirms that the marker of tumor metabolism is aerobic glycolysis rather than the mitochondrial oxidation of pyruvate ( Bencze et al, 2021 ; Wang, Wang & Tang, 2021 ; Wen et al, 2021 ). Studies have suggested that mitochondrial function is weakened by the inhibition of PDC, causing metabolic changes in tumor cells.…”
Section: Introductionmentioning
confidence: 72%
“…All of the Cxcl3, Ccl3, Ccl4, and Icam1 play an important role in the migration of neutrophils [ 38 , 39 , 40 , 41 ]. It is worth noting that the expression of Il1rn, as an anti-inflammatory gene [ 42 ], was up-regulated in the CLP group, which may be caused by auto-protective regulation. Maresin1 can significantly reduce the expression of the Cxcl3, Ccl3, Ccl4, and Icam1 genes in the Neutrophil3-Cxcl3 subpopulation, which may be an important mechanism by which Maresin1 regulates neutrophil function, and also provides a possible intervention target for the treatment of septic lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that physical exercise improves organ dysfunction by reducing systemic inflammation in sepsis patients. Wang et al (2021) found that aerobic exercise decreased lung neutrophil content and the mRNA expression levels of IL-6, TNF-α, Glu1, CXCL-1, and HMGB1 in the lung to improve respiratory dysfunction. Shimojo et al (2019) showed that swimming decreased serum inflammatory cytokines and increased anti-inflammatory cytokines by decreasing dopamine.…”
Section: Molecular Mechanisms Of Physical Exercise In Sepsis Treatmentmentioning
confidence: 95%
“…Here, we discuss whether physical exercise affects the outcomes of sepsis. Based on experimental models, several studies have suggested that regular exercise alters the morbidity of sepsis and increases the survival rate ( Sossdorf et al, 2013 ; Kim and Kang, 2019 ; Wang et al, 2021 ). In a clinical study, Wang et al (2014) indicated an association between physical exercise preconditioning and susceptibility to sepsis.…”
Section: Effects Of Physical Exercise On Multiple Organ Function and ...mentioning
confidence: 99%